Oceanographic Data of the 21st Japanese Antarctic Research Expedition from November 1979 to April 1980 - マツモト, クニオ; ミネ, マサユキ; MATSUMOTO, Kunio; MINE, Masayuki (National Institute of Polar Research, 1982)
P(論文) departmental bulletin paper